Case report describing balloon dilatation as a treatment for acute intraprosthetic regurgitation immediately following implantation of a SAPIEN‐3 transcatheter aortic valve. Issue 6 (17th June 2021) - Pal, Nikhil; Chew, Derek; Sinhal, Ajay
Abstract: Acute intraprosthetic regurgitation is a rare but potentially devastating complication following the transcatheter aortic valve implantation; here, balloon dilatation could provide a potential treatment option for these patients. Abstract : Acute intraprosthetic regurgitation is a rare but potentially devastating complication following the transcatheter aortic valve implantation; here, balloon dilatation could provide a potential treatment option for these patients.